Comportamento ingestivo de novilhas e terneiras de corte recriadas em campo nativo no período de outono-inverno - Carvalho, Thiago Henrique Nicola de (2011)
A experiment, in the period May- September 2011, was conducted in an area of Universidade Federal de Santa Maria studying the ingestive behavior of beef heifers and calves in a natural grassland of Rio Grande do Sul, under rotational grazing with different intervals among grazing. The intervals among grazing was determinated by the thermal sums of 375 and 750 degree-days for each treatment. Grazing, leisure and rumination times, time spent in the supplementation and water troughs was evaluated on three occasions using visual assessment periods of 24 uninterrupted hours. Bite rates, feed stations and number of steps between stations were evaluated in two observations, one at the beginning and another at the end of the experiment. No differences were found among animal categories for these measures. There were differences in grazing and leisure times, between treatments, on the last evaluated period and could be attributed to differences between forage mass. Number of feed stations was different between periods and differed between treatments only in the second evaluation. The number of steps between stations was different between the two periods with only difference between treatments in the first assessment. Bite rate varied among the treatments in both evaluations. It was concluded that differences in sward structure, caused by the treatments, affected feeding behavior of both categories, and there were no differences between them.